A systematic review protocol: Efficacy and safety of nitrous oxide in analgesia in burn patients with dressing change - Weifeng Wang; Xianli Meng; Yan Zhao; Wei Gong; Xiaochen Jiang; Wenjuan Cao; Xueling Qiu; Chenxi Sun; Fan Sun; Yuchen Wang; Lu Tang (PLoS ONE, 2026)
Background To alleviate pain in burn patients during dressing changes, it is necessary to identify an effective analgesic method. Conventional opioid analgesics have many limitations. Nitrous oxide is a fast-acting, safe and reversible inhaled analgesic gas. This systematic review will evaluate the effectiveness and safety of nitrous oxide in the treatment of pain during dressing changes in burn patients. Method The protocol was developed according to the PRISMA-P checklist and registered on PROSPERO (CRD42024550197). A systematic search will be performed in the following databases: PubMed, EMBASE, Web of Science, Cochrane Library to identify clinical trials comparing nitrous oxide inhalation with standard care in pain management during dressing changes in burn wounds. The search of all databases will be conducted on October 15, 2025.Our search scope will include studies published between each database creation and search date.Two researchers will independently screen studies, extract data, and evaluate study quality using the Risk of Bias2 tool. Primary outcomes will include pain, anxiety, side effects, among others.R statistical software (version 4.3.1) and R studio will be used to perform meta-analyses.Effect size will be expressed by 95% confidence interval (Cl) of weighted mean difference (MD) and risk ratio (RR). Subgroup analyses and sensitivity analyses will be performed to explore sources of heterogeneity and assess the robustness of the results.Publication bias will be assessed using funnel plot and Egger test. We will use the Grading of Recommendation, Evaluation, Development and Evaluation (GRADE) to assess the quality of the evidence. Discussion Operative pain has always been a difficult problem for burn patients. This study will evaluate the analgesic effect of nitrous oxide on dressing change in burn patients through comprehensive search and rigorous methods, and provide evidence support for clinical decision-making.